2011
DOI: 10.1002/jbm.a.33295
|View full text |Cite
|
Sign up to set email alerts
|

Biological response of endothelial cells to diamond‐like carbon‐coated NiTi alloy

Abstract: Diamond-like carbon (DLC) coatings were deposited on nearly equiatomic nickel-titanium (NiTi) alloy by arc-enhanced magnetron sputtering. The microstructure, surface morphology, chemical composition, surface free energy, protein adsorbance, and leach amount of Ni ions were assessed by Raman spectroscopy, high-resolution transmission electron microscopy (HR-TEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), contact angle measurements, micro BCA™ protein assay kit, and inductively coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In brief, cells (1×10 4 ) were seeded in 96-well culture plates and cultured overnight. The cells were treated with different concentrations of DHA (0, 10, 20, 40 and 80 µM) for 24 h, and the CCK-8 solution was added to each well and incubated for an additional 4 h. The absorbance at 450 nm was measured by Microplate reader (BioTek Instruments, Inc.) (13).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, cells (1×10 4 ) were seeded in 96-well culture plates and cultured overnight. The cells were treated with different concentrations of DHA (0, 10, 20, 40 and 80 µM) for 24 h, and the CCK-8 solution was added to each well and incubated for an additional 4 h. The absorbance at 450 nm was measured by Microplate reader (BioTek Instruments, Inc.) (13).…”
Section: Methodsmentioning
confidence: 99%
“…DLC coatings deposited on an equiatomic nickel-titanium (NiTi) alloy inhibited the release of Ni ions from the NiTi substrate, enhancing its biosafety. The adhesion, morphology, and viability of endothelial cells (ECs) showed to be better on DLC coatings than on bare NiTi alloy, leading to faster endothelialization after surgical implantation [184]. Mononuclear macrophages (THP-1 monocytes) cell proliferation revealed no significant promotion between TiN coated and uncoated stainless steel; however, pro-inflammatory TNF-α levels were found to be higher, indicating better biocompatibility [185].…”
Section: Dlc Biocompatibilitymentioning
confidence: 98%
“…Lack of nickel can cause diabetes, uremia, kidney failure, and other diseases. Studies have shown that Ni 2+ can effectively kill bacteria ( Yasuyuki et al, 2010 ), but excessive Ni 2+ will cause cytotoxicity ( Lü et al, 2009 ; Hang et al, 2012 ). A recent study showed that Ni 2+ released from NiTi alloys could exhibit antibacterial properties ( Ohtsu et al, 2017 ).…”
Section: Nanomaterials Loadingmentioning
confidence: 99%